On the Regularized Trace of a Differential Operator of Sturm-Liouville Type - Gul, Erdal (UNIV NIS, FAC SCI MATH, 2022)
In this work, we study a spectral problem for the abstract Sturm-Liouville operator with a bounded operator coefficient V(t) and with periodic boundary conditions on the interval [0, pi], and we present a regularized trace formula for this operator.
Keywords: Hilbert space; Trace-class operator; Spectrum; Regularized trace; Mathematics